“We are the Arctic”: identities at the Arctic Winter Games 2016 - Thomsen, Robert C.; Ren, Carina; Mahadevan, Renuka (Arctic Anthropology, 2018)
In this article, we explore the 2016 Arctic Winter Games (AWG) as a site for arctic, Indigenous, and national identity building, drawing on fieldwork from the planning and execution of AWG 2016 and surveys conducted with participant and stakeholder groups. We show that although the AWG 2016 event is seemingly a contranational sports competition in the Olympic modality, and thus a vehicle for traditional national identity manifestations, it also caters to other collective identity constructions. In our analysis, we present and discuss four collective identity manifestations at the AWG 2016: "panarctic," "contranational/regional," Indigenous, and "autocommunicating" national identity. Our study suggests that the AWG event not only reproduces existing national identities or the singular panarctic identity that organizers actively promote, but works as a catalyst for the manifestation of other identity positions also. In practice, competition at this sporting event extends to identity discourses competing for hegemony, but the games also create spaces for identity negotiation and willful identity entanglement.